Penanaman Mangrove dan Kegiatan Coastal Clean-Up terhadap Pelestarian Lingkungan Pesisir di Kabupaten Belu Nusa Tenggara Timur - Kusnendi, Faizal Shofwan; Hadisugelar, Danar; Sugiri, Sugiri; Fadillah, Resti (Unity Academy, 2025)
Mangrove planting and coastal clean-up activities at Sukaer Laran Beach, Kenebibi Village, Belu Regency, East Nusa Tenggara, were carried out with the aim of rehabilitating coastal ecosystems and raising public awareness of the importance of environmental conservation. The activity involved lecturers and 25 cadet students from the Military Logistics Vocational Faculty (FVLM), Plantation Crop Cultivation Study Program, in collaboration with KPP Pratama Atambua. The program employed an andragogical approach, incorporating discussion and service learning methods, including a public outreach session on the importance of mangroves and coastal conservation, symbolic distribution of mangrove seedlings, planting activities, and a collective beach clean-up. The results showed increased community participation and successful rehabilitation of the coastal area through mangrove planting and waste reduction. This activity had a positive impact on coastal environmental sustainability and strengthened the role of local communities in preserving coastal ecosystems. Therefore, similar programs should continue to be supported to maintain environmental sustainability in East Nusa Tenggara's coastal regions.